Metamorphoses of Modern Court Culture. Mechanisms, Agents, Channels of Communication - Kuras, Katarzyna (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
This article presents the mechanisms, the agents of transfer, and the channels of communication responsible for the processes of cultural exchange within the network of European courts in 16th–18th centuries. It focuses on the practical conditions of the exchange, showing the character of court culture, the issue of meetings between rulers’ courts and the importance of the monarchs’ matrimonial policy. The presentation of the agents of transfer comprises the various groups who participated in the processes of cultural transfer, including members of dynasties, travelers and hired artists. This picture is complemented by the analysis of the channels of communication based on the circulation of the printed and written word (including court periodicals, accounts of ceremonies). The overview of the issue aims to show court culture in a dynamic context and to highlight its constant and changing elements.